Die Komplementsätze mit den Subjunktoren ČTO ‘dass’ und KAK ‘wie’ im Gegenwartsrussischen unter einem partiellen Vergleich mit ihren deutschen Entsprechungen - Kiklewicz, Aleksander; Kotin, Michail L. (Przegląd Wschodnioeuropejski, 2026)
The subject of the study are the object clauses with the complementizers ČTO ‘that’ and KAK ‘how’ in modern Russian, with a partial comparison to their German counterparts. The study concerns the alternations of syntactic actants, implemented in the form of a dependent clause. The authors focus on one type of such semantically conditioned alternations. For this purpose, the authors compare alternative syntactic forms of sentential actants with the Russian complementizers ČTO | KAK and the German equivalents DASS | WIE. The analysis shows that each type of sentential actant allows for different valency classes, and there are also differences between the studied languages: German and Russian.